A Study of Dynamic Loading and Unloading Damage of Fiber-Reinforced Concrete under Confining Pressure - Lin, Chao; Rao, Li; Zhang, Cheng-Lin; Yang, Zhi-Wen; Chen, Fang; You, Qing; Tan, Xian-Jun (Geofluids, 2022)
Considering the influence of confining pressure in the actual service environment of concrete in underground projects, the damage characteristics of fiber-reinforced concrete under the action of confining pressure are evaluated according to the variation of measured permeability values by means of a triaxial ultralow permeability damage test system. The tests were carried out according to the stress loading and unloading paths of 1⟶5⟶10⟶15⟶20⟶10⟶5⟶1 MPa for an axial pressure when the confining pressure value was 1 MPa and kept constant. Firstly, the damage permeability of the fiber-reinforced concrete specimens was verified to be significantly lower than that of the ordinary concrete under the same confining pressure. Secondly, by conducting single loading and unloading tests at different loading rates (0.5, 1.0, 1.5, and 3.0 MPa/s), it was confirmed that the loading rate had a significant effect on the damage cracking of the specimens, with the faster the loading rate, the more pronounced the damage characteristics. Finally, a triaxial cyclic dynamic load test with a confining pressure value of 1 MPa and an axial loading speed of 1.5 MPa/s was carried out, revealing that the damage characteristics of the test blocks changed from elastic deformation to obvious plastic deformation damage as the number of loading times increased.